Pharmacokinetic Studies with FVIII/von Willebrand Factor Concentrate Can Be a Diagnostic Tool to Distinguish between Subgroups of Patients with Acquired von Willebrand Syndrome - Luboshitz, J.; Lubetsky, A.; Schliamser, L.; Kotler, A.; Tamarin, I.; Inbal, A. (Thrombosis and Haemostasis, 2001)
Acquired von Willebrand syndrome (AVWS) has been associated mainly with monoclonal gammopathy of uncertain significance (MGUS), clonal lymphoproliferative or myeloproliferative disorders and autoimmunity. In the present work we studied 6 patients with AVWS: four with MGUS IgG (λ or κ), one with small lymphocytic lymphoma and one with agnogenic myeloid metaplasia (AMM). All the patients underwent a pharmacokinetic analysis at presentation in order to study potential differences in recovery, clearance (CL) or terminal half-life (THL) following administration of von Willebrand factor (VWF) concentrate. In all the patients with AVWS an increase in clearance and a decrease in THL was observed as compared to these parameters in patients with hereditary type 3 von Willebrand disease (VWD). No difference in recovery was observed among the groups. The increase in clearance and the decrease in THL were significantly more pronounced in the group of MGUS patients (57.93 ± 25.6 ml/h/kg, and 1.39 ± 0.5 h, respectively) as compared to these parameters in the AMM (8.06 ml/h/kg, and 6.96 h, respectively) or the lymphoma (4.76 ml/h/kg, and 6.76 h, respectively) patients (p = 0.03 for clearance and 0.001 for THL). These data indicate that the pharmacokinetic analysis can be a useful tool to distinguish between MGUS-related and other causes of AVWS, and to plan an appropriate treatment accordingly.
Keywords: Acquired von Willebrand; pharmacokinetics